Intra-Rater and Inter-Rater Reliability of Pressure Pain Algometry of the Sural and Tibial Nerves in Asymptomatic Elite Youth Footballers - Daniel Richards; Simon Jones; Josh Jeffery; Matthew Lowe; Mark Godwin; Matthew Willett (MDPI AG, 2021)
Ankle injuries are highly prevalent in elite youth footballers and increase the mechanosensitivity of the local neural tissue, which may predispose athletes to re-injury and prolong rehabilitation periods. Increased neural mechanosensitivity presents clinically as altered pain pressure thresholds (PPTs) which are measured with pressure algometry. The purpose of this study was to determine the intra-rater and inter-rater reliability of PPTs of the ankle neural tissue in asymptomatic elite youth football players. Three raters utilised a digital algometer to evaluate the PPTs of the Sural and Tibial nervous tissue at the ankle of elite youth male footballers. Intraclass correlation coefficients (ICCs) with 95% confidence intervals (CI) were calculated to assess intra-rater and inter-rater reliability and Bland-Altman figures were plotted to enable visual evaluation of measurement error with a significance level of p < 0.05. Thirty-four players (16-18 years old) were assessed. Excellent intra-rater (Tibial ICC 0.88 (0.76-0.94); Sural ICC 0.89 (0.79-0.95)) and good inter-rater reliability (Tibial ICC 0.66 (0.40-0.82); Sural 0.71 (0.50-0.85)) was demonstrated. Bland-Altman plots demonstrated low levels of measurement error. Pressure algometry can be utilised clinically to accurately evaluate the PPTs of the Tibial and Sural nervous tissue at the ankle in asymptomatic elite male youth footballers.